Potentially pathogenic Escherichia coli from household water in peri-urban Ibadan, Nigeria. (8th July 2022) - Rabiu, Akeem Ganiyu; Falodun, Olutayo Israel; Fagade, Obasola Ezekiel; Dada, Rotimi Ayodeji; Okeke, Iruka N.
Abstract: Feco-orally transmitted infectious diseases are common in Nigeria where the potable water access is poor. In the south-western Nigerian Ibadan metropolis, supply of municipal water is meagre as residents depend on household wells and boreholes. The likelihood of fecal contamination of household water sources in Ibadan was examined longitudinally to quantify and understand its impact. Well and borehole water samples aseptically collected from 96 households in Ibadan were assessed for total heterotrophic counts (THCs), total coliform counts (TCCs) and total Escherichia coli counts (TECs) using a pour plate technique. E. coli were identified by uidA and whole-genome sequencing using Illumina technology, whereas virulence factors were predicted using VirulenceFinder. There was season-independent abundance of THC and TCC in the well and borehole with a significant recovery of E. coli in the wells during the wet season compared to the dry season ( P = 0.0001). Virulence genes associated with pathogenic E. coli were identified in 13 (52%) strains with one E. coli each classified as extra-intestinal E. coli, avian pathogenic E. coli and enteroaggregative E. coli . High heterotrophic and coliform counts, with rainfall-driven E. coli contamination revealed that the water sources evaluated in this study are unfit for consumption. HIGHLIGHTS: Spatio-temporal analyses of bacterial counts were used to investigate drinking water quality in Ibadan, Nigeria. Rainfall-driven fecal contamination revealed that well water sources were unfit for drinking. A novel Escherichia coli sequence type, ST13028, was found in a household well water. Potentially virulent extra-intestinal, avian pathogenic and enteroaggregative E. coli strains were recovered from household wells.